Power Allocation For Dynamic Fractional Frequency Reuse (DFFR) In Downlink LTE-A System - Noor Shahida, Mohd Kasim; Rosdiadee, Nordin; Mahamod, Ismail (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
Network MIMO is a feasible technique that can significantly improve the performance of wireless communication systems by canceling the Inter-cell Interference (ICI). Dynamic Fractional Frequency Reuse (DFFR) is the technique to mitigate ICI in LTE-Advanced system, which improve throughput and capacity, especially for the cell-edge users (CEUs). Recent research has shown that the impact of DFFR scheme on system performances has already studied and can provide significant gains in term of outage probability and network sum rate throughput. This paper presents a performance investigation of a DFFR scheme in a Network MIMO configuration based on an LTE-A downlink transmission environment. This paper also aims to enhance cell edge throughput and capacity by improving water filling algorithm for power allocation (PA). The proposed PA strategy is to maximize the performance of CEUs which commonly incur considerable ICI. Furthermore, the proposed method has been compared to the Frequency Reuse, Fractional Frequency Reuse (FFR) and other conventional DFFR schemes. Results show that the proposed scheme present superior performances of the throughput by 60% and capacity by 42% compared to the other schemes.